Age no bar: A CIBMTR analysis of elderly patients undergoing autologous hematopoietic cell transplantation for multiple myeloma. Issue 23 (23rd September 2020) - Munshi, Pashna N.; Vesole, David; Jurczyszyn, Artur; Zaucha, Jan Maciej; St. Martin, Andrew; Davila, Omar; Agrawal, Vaibhav; Badawy, Sherif M.; Battiwalla, Minoo; Chhabra, Saurabh; Copelan, Edward; Kharfan‐Dabaja, Mohamed A.; et al.
Abstract : Background: Upfront autologous hematopoietic stem cell transplantation (AHCT) remains an important therapy in the management of patients with multiple myeloma (MM), a disease of older adults. Methods: The authors investigated the outcomes of AHCT in patients with MM who were aged ≥70 years. The Center for International Blood and Marrow Transplant Research (CIBMTR) database registered 15, 999 patients with MM in the United States within 12 months of diagnosis during 2013 through 2017; a total of 2092 patients were aged ≥70 years. Nonrecurrence mortality (NRM), disease recurrence and/or progression (relapse; REL), progression‐free survival (PFS), and overall survival (OS) were modeled using Cox proportional hazards models with age at transplantation as the main effect. Because of the large sample size, a P value <.01 was considered to be statistically significant a priori. Results: An increase in AHCT was noted in 2017 (28%) compared with 2013 (15%) among patients aged ≥70 years. Although approximately 82% of patients received melphalan (Mel) at a dose of 200 mg/m 2 overall, 58% of the patients aged ≥70 years received Mel at a dose of 140 mg/m 2 . On multivariate analysis, patients aged ≥70 years demonstrated no difference with regard to NRM (hazard ratio [HR] 1.3; 99% confidence interval [99% CI], 1‐1.7 [ P = .06]), REL (HR, 1.03; 99% CI, 0.9‐1.1 [ P = 0.6]), PFS (HR, 1.06; 99% CI, 1‐1.2 [ P = 0.2]), and OS (HR, 1.2; 99% CI, 1‐1.4 [ P = .02]) compared with the reference group (those aged 60‐69 years). In patients aged ≥70 years, Mel administered at a dose of 140 mg/m 2 was found to be associated with worse outcomes compared with Mel administered at a dose of 200 mg/m 2, including day 100 NRM (1% [95% CI, 1%‐2%] vs 0% [95% CI, 0%‐1%]; P = .003]), 2‐year PFS (64% [95% CI, 60%‐67%] vs 69% [95% CI, 66%‐73%]; P = .003), and 2‐year OS (85% [95% CI, 82%‐87%] vs 89% [95% CI, 86%‐91%]; P = .01]), likely representing frailty. Conclusions: The results of the current study demonstrated that AHCT remains an effective consolidation therapy among patients with MM across all age groups. Abstract : Upfront autologous hematopoietic stem cell transplantation (AHCT) remains an important therapy for the management of patients with multiple myeloma, which is a disease of older adults. The results of the current large database study confirm that AHCT remains an effective consolidation therapy in fit older adults aged ≥70 years.